Cough, a vital reflex. mechanisms, determinants and measurements - Andrani, Francesco; Aiello, Marina; Bertorelli, Giuseppina; Crisafulli, Ernesto; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2019)
Cough is a natural defense mechanism that protects the respiratory tract from inhaling foreign bodies and by clearing excessive bronchial secretions. As a spontaneous reflex arc, it involves receptors, an afferent pathway, a center processing information, an efferent pathway and effectors. The determinant factor of cough efficacy is the operational volume of the lung, which in turn relies on the strength and coordination of respiratory and laryngeal muscles as well as on lung mechanics. Respiratory muscle weakness and dysfunction as well as expiratory flow limitation and lung hyperinflation may occur in some neuromuscular disorders and in obstructive airway diseases, respectively. Accordingly, all these diseases may show an ineffective cough. In this brief overview, we deal with the determinants of the cough efficacy and the clinical conditions affecting cough efficacy as well as the cough’s efficacy measurements in clinical setting.